The Impact of Natural Antioxidants on the Regenerative Potential of Vascular Cells - Shafi, Shahida; Ansari, Hifzur Rahman; Bahitham, Wesam; Aouabdi, Sihem (Frontiers in Cardiovascular Medicine, 2019)
With advances in technology, the impact of natural antioxidants on vascular cell regeneration is attracting enormous attention as many current studies are now exploring the clinical potential of antioxidants in regenerative medicine. Natural antioxidants are an important step for improving future treatment and prevention of various diseases such as cardiovascular, cancer, neurodegenerative and diabetes. The use of natural antioxidants which have effects on several types of stem cells with the potential to differentiate into functional endothelium and smooth muscle cells (known as vascular progenitors) for vascular regeneration might override pharmaceutical and surgical treatments. The natural antioxidant systems comprise of several components present in fruits, vegetables, legumes, medicinal plants and other animal-derived products that interact with reactive free radicals such as oxygen and nitrogen species to neutralize their oxidative damaging effects on vascular cells. Neutralization by antioxidants involves the breaking down of the oxidative cascade chain reactions in the cell membranes in order to fine-tune the free radical levels. The effect of natural antioxidants on vascular regeneration includes restoration or establishment of new vascular structures and functions. In this review, we highlight the significant effects of natural antioxidants on modulating vascular cells to regenerate vessels, as well as possible mechanisms of action and the potential therapeutic benefits on health. The role of antioxidants in regenerating vessels may be critical for the future of regenerative medicine in terms of the maintenance of the normal functioning of vessels and the prevention of multiple vascular diseases.